2016
DOI: 10.1371/journal.pone.0150302
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Classification, a Practical Tool for Mangrove Restoration

Abstract: Mangrove restoration projects, aimed at restoring important values of mangrove forests after degradation, often fail because hydrological conditions are disregarded. We present a simple, but robust methodology to determine hydrological suitability for mangrove species, which can guide restoration practice. In 15 natural and 8 disturbed sites (i.e. disused shrimp ponds) in three case study regions in south-east Asia, water levels were measured and vegetation species composition was determined. Using an existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 59 publications
2
25
0
3
Order By: Relevance
“…Individual species have differing tolerances to specific biogeochemical factors and gradients present across the intertidal area (Saenger, 2002). These include salinity, soil type, soil anoxia, sulphate levels, nutrient levels, pH, wave energy, temperature, light levels, inundation regimes (Alongi, 2009;Tomlinson, 2016;van Loon et al, 2016), tides and wind distribution of propagules and seeds (van der Stocken et al, 2012), and species-selective predation by herbivores (Elster, 2000;Sousa et al, 2003). Species therefore exhibit differing 'preferences' for elevation and location within the intertidal zone (Duke, 2006;Snedaker, 1982;Tomlinson, 2016).…”
Section: Technical Reasons For Previous Failuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual species have differing tolerances to specific biogeochemical factors and gradients present across the intertidal area (Saenger, 2002). These include salinity, soil type, soil anoxia, sulphate levels, nutrient levels, pH, wave energy, temperature, light levels, inundation regimes (Alongi, 2009;Tomlinson, 2016;van Loon et al, 2016), tides and wind distribution of propagules and seeds (van der Stocken et al, 2012), and species-selective predation by herbivores (Elster, 2000;Sousa et al, 2003). Species therefore exhibit differing 'preferences' for elevation and location within the intertidal zone (Duke, 2006;Snedaker, 1982;Tomlinson, 2016).…”
Section: Technical Reasons For Previous Failuresmentioning
confidence: 99%
“…These features greatly affect planting outcomes (Aung et al, 2011;Elster, 2000;Hashim et al, 2010;Kairo et al, 2001;Lewis, 2005). Duration of inundation is particularly important (van Loon et al, 2016).…”
Section: Technical Reasons For Previous Failuresmentioning
confidence: 99%
“…Other studies have demonstrated the importance of reporting gross land cover statistics when evaluating change dynamics, including mangroves (Thomas et al 2017, Estoque et al 2018, Gaw et al 2018, De Alban et al 2019. This is because gross land cover change estimates provide essential information on transitions among land cover classes unavailable through net change studies, leading to a more robust analysis of the drivers of land cover change (Pontius et al 2004, Aldwaik and, which is especially important for relatively dynamic mangrove communities since they are amenable to rapid deforestation (loss) but can also rapidly regenerate (gain) when biophysical conditions are appropriate (Lewis 2005, Loon et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of the topography may increase the strength of the tidal ebb and flow as topographic levels are reduced [33]. In Zone II, the hydrological gradient produced by tides and by the internal circulation caused by the wind spontaneously carved secondary tidal channels <1 m in width and <0.5 m in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Some proposed using hydraulic modeling to simulate flooding to perform hydrological and sedimentological restoration [32], while others considered the presence of mangrove species to classify the hydrological patterns and to make decisions on restoration actions [33]. Moreover, strategies aimed to improve mangrove recruitment have been applied.…”
Section: Introductionmentioning
confidence: 99%